Maintenance Therapy with Partially Hydrolyzed Guar Gum in the Conservative Treatment of Chronic Anal Fissure: Results of a Prospective, Randomized Study. (25th June 2014) - Brillantino, Antonio; Iacobellis, Francesca; Izzo, Giuseppe; Di Martino, Natale; Grassi, Roberto; Renzi, Adolfo
Abstract : Purpose . This study was designed to evaluate the role of maintenance therapy with partially hydrolyzed guar gum (PHGG) after topical application of glyceryl trinitrate (GTN) in the conservative treatment of chronic anal fissure (CAF). Methods . From all the patients with CAF observed during the study period, 165 subjects with healed CAF after standard therapy with topical GTN 0.4% ointment were randomized to receive (group II) or not (group I) maintenance therapy with PHGG for 10 months. Clinical and manometric followup was carried out 6 and 12 months after treatment. Results . At six-month followup, median visual analogue scale score was significantly higher in group I if compared with group II. The success and recurrence rate at 12-month followup were, respectively, 38.3% (28/73) in group I versus 58.5% (41/70) in group II (P = 0.019 ; Fisher's exact test) and 30.2% (13/43) in group I versus 14.5% (7/48) in group II (P = 0.0047 ; Fisher's exact test). Conclusion . The maintenance therapy with PHGG in patients with healed CAF after chemical sphincterotomy by topical application of GTN 0.4% ointment seems associated with a significant reduction of recurrence rate and with a significant increase of success rate at 12-month followup.